Langkah Manajerial Kepala Sekolah dalam Meningkatkan Kompetensi Guru Agama Islam di Madrasah Aliyah Muhammadiyah Curup - Lukman Asha (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Law No. 14 of 2005 concerning Teachers and Lecturers, has inspired the Principal of the Madrasah Aliyah Muhammadiyah School (MAM) Curup. The inspiration was manifested in the managerial step of increasing four main competencies, namely: pedagogical competence, professional competence, personality competence, and social competence. In connection with the managerial step, this paper aims to describe; (1) school principal management in improving teacher competency; (2) the success of the principal's management in improving teacher competency; (3) inhibiting factors and principals management solutions in improving teacher competency. This research is in the form of qualitative, using data collection methods in the form of observation, interviews, and documentation. The results showed that the principal's management strategy in improving teacher competency in MAM Curup, namely: First, School Principal Management in improving Islamic education teacher competencies as follows: (1) Involving teachers in training, training and seminars, (2) Promoting discipline, (3) Motivating teachers, through motivation from school principals, becomes the spirit for teachers to improve improvements in educational innovation as a tangible form of developing competencies, (4) Implementation of Supervision. Secondly, the application of the principal's management in improving teacher competence greatly influences the competency of PAI teachers in MAM Curup, namely that teachers have implemented the five basic competency standards that are best governed by the government. Third, the barriers and solutions of the principal's management in developing the competence of Islamic education teachers in MAM Curup, namely: The role of parents has not been seen in the personal / karaker of each student, then together with the teaching time of the teacher with the training time in increasing teacher competency